Legal Protection Toward Balinese Arak as Intangible Cultural Heritage - I.B. Deva Harista Setiawan; Putu Aras Samsithawrati (University of Udayana, 2023)
The purpose of this study is to determine the regulation of traditional drinks as intangible cultural heritage and to analyze the protection of Balinese Arak as one of the traditional knowledge that is used commercially in the context of intangible cultural heritage. This article uses normative legal research with statute, analytical, and conceptual approaches. The results showed that the regulation of traditional drinks as intangible cultural heritage, specifically traditional knowledge, is regulated in several laws and regulations such as the Convention for the Safeguarding of the Intangible Cultural Heritage, Law No. 5 of 2017 on Advancement of Culture, Bali Regional Regulation Number 4 of 2020 on Strengthening and Promotion of Balinese Culture as well as Bali Governor Regulation Number 1 of 2020 on the Management of Balinese Fermented and/or Distilled Drink. Although IHC is for preservation, however, it can be interpreted that Law No. 5 of 2017 on Advancement of Culture is more than just preservation as it already regulates in general the commercialization of the object of cultural advancement. The protection of Balinese Arak as one of the traditional knowledge that is used commercially is protected under Articles 37 and 38 of Law No. 5 of 2017 on Advancement of Culture where the Indonesian Government gives permission to big industry and/or foreign parties who want to take advantage of Indonesian cultural advancement objects on the condition that they must meet the principle of benefit sharing as a form of protection.